2022
DOI: 10.4236/ojog.2022.126049
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Perceptions Influencing Cervical Cancer Screening among Women in Kitwe District, Copperbelt Province, Zambia

Abstract: Background: Cervical Cancer is one such a disease that remains with high mortality unless prevented or detected early and managed. It is one of the most common cancers of the child bearing age between 20 and 45 years world over. It is rated as the second most prevalent cancer among women. There is high consensus among various scholars that high quality screening, effective treatment and routine follow-up care are cardinal in helping women. The main objective of the study was to identify the factors influencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(25 reference statements)
0
0
1
Order By: Relevance
“…This result is similar to that of John-Akinola et al [8] in Nigeria and Ghosh et al [9] in India, who respectively had 77% and 77.2% poor knowledge regarding CC prevention. In contrast to our study, Daka et al [10] in Zambia reported 77.6% of women who had a good knowledge about CC. This difference could be explained by the implementation and implementation of the See and Treat programme for CC screening throughout the country, the training of health workers.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is similar to that of John-Akinola et al [8] in Nigeria and Ghosh et al [9] in India, who respectively had 77% and 77.2% poor knowledge regarding CC prevention. In contrast to our study, Daka et al [10] in Zambia reported 77.6% of women who had a good knowledge about CC. This difference could be explained by the implementation and implementation of the See and Treat programme for CC screening throughout the country, the training of health workers.…”
Section: Discussioncontrasting
confidence: 99%